Self–other relations in biodiversity conservation in the community: representational processes and adjustment to new actions - Mouro, C.; Castro, P. (Journal of Community and Applied Social Psychology, 2016)
This research explores the simultaneous role of two Self-Other relations in the elaboration of representations at the micro-and ontogenetic levels, assuming that it can result in acceptance and/or resistance to new laws. Drawing on the Theory of Social Representations, it concretely looks at how individuals elaborate new representations relevant for biodiversity conservation in the context of their relations with their local community (an interactional Other) and with the legal/reified sphere (an institutional Other). This is explored in two studies in Portuguese Natura 2000 sites where a conservation project calls residents to protect an at-risk species. Study 1 shows that (i) agreement with the institutional Other (the laws) and meta-representations of the interactional Other (the community) as approving of conservation independently help explain (at the ontogenetic level) internalisation of conservation goals and willingness to act; (ii) the same meta-representations operating at the microgenetic level attenuate the negative relation between ambivalence and willingness to act. Study 2 shows that a meta-representation of the interactional Other as showing no clear position regarding conservation increases ambivalence. Findings demonstrate the necessarily social nature of representational processes and the importance of considering them at more than one level for understanding responses to new policy/legal proposals.